The Real Price Of Parking Policy - Jos van Ommeren; Derk Wentink; Jasper Dekkers (Tinbergen Institute, 2009)
This paper is the first to empirically examine the residents' willingness to pay for on-street parking permits as well as the cost of cruising using an identification methodology based on house prices for Amsterdam. The average cost of cruising is exteuro1.30 per day. The average residents' willingness to pay for a parking permit is exteuro8 per day. Further, we show that the introduction of paid parking in a neighborhood decreases house prices in this neighbourhood.
Keywords: R48; 330; on-street parking; cruising; parking policy; parking permits; Ruhender Verkehr; Willingness to pay; Amsterdam